The Developments and Attitude of Turkey in the Geography of Nakhchivan, Azerbaijan and Armenia in Terms of Karabakh Axis, from the Process of Disintegration of the USSR Until the Setting up the CIS (Commonwealth of Independence States) (1987 October-1991 December) - Erdem KARACA (Gazi Akademik Bakış)
After dispersing of Soviet Union, Karabakh Armenians first made an effort for their freedom then tried to be connected with Armenia. The situation that supported by Armenia caused a huge conflict between Azerbaijan and Armenia. Turkey has sought to play a constructive interference to solve the emergent hitches which is impossible to avoid from this problem. “The Turkish National Assembly recording journal” and “Hürriyet newspaper” are the main sources in this study. Subject headings are like this: 1. Introduction: Karabakh, 2. Karabakh-Ralated Caos while Soviet Union Separating: Demonstration, Action, Cconflict Process, 3. Karabakh’s Bonding to Moscow and Unavoidable Caos, 4.The New Way of Seeking of Turkey, Azerbaijan and Armenia, 5. The Failure of the Union: Liberation Movements in Caucasians, 6. Abolition of Soviet Union and New Consortium (CIS) while Conflict Running on Between Azerbaijan and Armenia, 7. Conlusion and Evaluation.